Effects of freezing and thawing on some agar parameters of Eucheuma spinnodum and gracilaria confervoides - Abelende, Ma. Orfa R.
Agar was extracted from two agar-containing red algae species namely Gracilaria confervoides and Euchema spinosum. Qualitative assessment was made on the agar extracts which included percentage yield, gel strenght, synerisis and hysteresis range. The quality of agar extracts derived from this study was compared to commercial agar-agar. The effects of each parameters, repeated freezing and thawing on agar were also investigated., Qualitative test showed that percentage yield from Gracilaria was higher than Euchema. Gel strenght and hysteresis range of agar from commercial sources and Gracilaria were higher compared to Euchema. On the other hand, syneresis range was highest in Euchema agar. Repeated freezing and thawing lowered percentage yield and syneresis but increased gel strenght and hysteresis of agar extracts from agar sources used.